Preschool education in the municipality of Floridablanca - Anaya Niño, Carolina; Espinel Sarmiento, Andrea Fernanda; Estévez Diettes, Marllin Paola (Rastros Rostros, 2024)
The pedagogical expedition has opened a space for us to participate in the route through the preschools of the municipality of Floridablanca, to learn about the socio-cultural, socio-affective and coverage conditions of preschool education, and also to investigate the conceptions and pedagogical practices of the teachers who guide the formation of children at this level.